2020
DOI: 10.3389/fnins.2020.558434
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Alteration of Brain Functional Network and Its Role in the Identification of Mild Cognitive Impairment

Abstract: Mild cognitive impairment (MCI) is generally regarded as a prodromal stage of Alzheimer's disease (AD). In coping with the challenges caused by AD, we analyzed resting-state functional magnetic resonance imaging data of 82 MCI subjects and 93 normal controls (NCs). The alteration of brain functional network in MCI was investigated on three scales, including global metrics, nodal characteristics, and modular properties. The results supported the existence of small worldness, hubs, and community structure in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 73 publications
3
19
0
Order By: Relevance
“…As a result, 36 articles met our inclusion criteria (13 AD, 14 MCI, and 9 combined AD/MCI articles) and were included in the quantitative synthesis. Thus, the total number of the final included articles was 36 (Balthazar, de Campos, Franco, Damasceno, & Cendes, 2014; Bi, Shu, Sun, & Xu, 2018; Challis et al, 2015; X. Chen et al, 2017; Dai et al, 2012; de Marco et al, 2017; de Vos et al, 2018; Dyrba et al, 2015; Hojjati et al, 2019; Hojjati, Ebrahimzadeh, Khazaee, & Babajani‐Feremi, 2017, 2018; X. Jiang, Zhang, & Zhu, 2014; Jin et al, 2020; Khazaee, Ebrahimzadeh, & Babajani‐Feremi, 2017; Kilian, Bröckel, Overmeyer, Dieterich, & Endrass, 2020; Koch et al, 2012; J. Lee et al, 2015; Y. Li, Wee, Jie, Peng, & Shen, 2014; Lisowska & Rekik, 2019; J. Liu, Pan, Wu, & Wang, 2020; Miao, Wu, Li, Chen, & Yao, 2011; Park et al, 2017; Qian, Zheng, Shang, Zhang, & Zhang, 2018; Qureshi et al, 2019; Schouten et al, 2016; Son, Kim, & Park, 2017; Suk, Wee, Lee, & Shen, 2015; Teipel et al, 2016; Teipel et al, 2017; Wee et al, 2012; Yokoi et al, 2018; Yu et al, 2017; L. Zhang et al, 2020; Y. Zhang, Zhang, Chen, Lee, & Shen, 2017; J. Zhao, Ding, Du, Wang, & Men, 2019; Zheng et al, 2019; Zhu et al, 2014) Overall, the articles had low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, 36 articles met our inclusion criteria (13 AD, 14 MCI, and 9 combined AD/MCI articles) and were included in the quantitative synthesis. Thus, the total number of the final included articles was 36 (Balthazar, de Campos, Franco, Damasceno, & Cendes, 2014; Bi, Shu, Sun, & Xu, 2018; Challis et al, 2015; X. Chen et al, 2017; Dai et al, 2012; de Marco et al, 2017; de Vos et al, 2018; Dyrba et al, 2015; Hojjati et al, 2019; Hojjati, Ebrahimzadeh, Khazaee, & Babajani‐Feremi, 2017, 2018; X. Jiang, Zhang, & Zhu, 2014; Jin et al, 2020; Khazaee, Ebrahimzadeh, & Babajani‐Feremi, 2017; Kilian, Bröckel, Overmeyer, Dieterich, & Endrass, 2020; Koch et al, 2012; J. Lee et al, 2015; Y. Li, Wee, Jie, Peng, & Shen, 2014; Lisowska & Rekik, 2019; J. Liu, Pan, Wu, & Wang, 2020; Miao, Wu, Li, Chen, & Yao, 2011; Park et al, 2017; Qian, Zheng, Shang, Zhang, & Zhang, 2018; Qureshi et al, 2019; Schouten et al, 2016; Son, Kim, & Park, 2017; Suk, Wee, Lee, & Shen, 2015; Teipel et al, 2016; Teipel et al, 2017; Wee et al, 2012; Yokoi et al, 2018; Yu et al, 2017; L. Zhang et al, 2020; Y. Zhang, Zhang, Chen, Lee, & Shen, 2017; J. Zhao, Ding, Du, Wang, & Men, 2019; Zheng et al, 2019; Zhu et al, 2014) Overall, the articles had low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…If the core nodes are attacked, the efficiency and stability of network information processing and transmission will be significantly reduced. Given that BC reflects the central roles of nodes in the overall information communication of the networks and has been extensively utilized in the hub analysis of brain networks (Wang, Li, Wang, Xian, & He, 2016; Zhang et al, 2020), we defined the hub regions of brain FC networks by identifying the nodal BC as the key index. We found similar global hub distributions among groups, suggesting that these key regions in brain networks are conserved throughout the development process and that small‐world networks can tolerate developmental alterations or disease (Wen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of imaging studies have confirmed that cerebellar Crus II and lobular IX are associated with cognitive networks (32,34,35), particularly with the default mode network (DMN) and fronto-parietal network (FPN) (36)(37)(38). The anterior cerebellum and lobule VIII are associated with movement, whereas the posterior cerebellum (i.e., lobule VI-Crus I, lobule Crus II-VIIB, and lobule IX) are critical for cognitive representation (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%